CONGENITAL LARYNGEAL STRIDOR: DIAGNOSTICS AND TREATMENT - A.Yu. Petrunichev; G.A. Novik; E.A. Tsvetkov (Педиатрическая фармакология, 2011)
Congenital laryngeal stridor is known as a separate disorder for 1,5 centuries. Its diagnostics presents difficulties because of its absense (over prevalence of mild cases) or very expensive and hard-to-reach diagnostic methods. This article represents the results of investigation and treatment of 369 patients with congenital noisy breathing. High frequency in population is revealed (4% totally and more than 40% of all cases of congenital stridor). We offer some new approaches (clinical, lab, X-ray and morphologic) and modified design of diagnostics that appears to be available, inexpensive and effective.Key words: congenital stridor, laryngomalacia, diagnostics, treatment, children.